A fungicide composition - Sijam, Kamaruzaman; Haron, Farah Farhanah; Omar, Dzolkhifli; Rahmani, Mawardi (2011)
The present invention relates to a fungicide composition comprising of 7% to 35% w/w of Allamanda concentrated liquid crude extract (ACLCE); 20% to 80% w/w of aqueous medium; 1% to 15% w/w of Alkylpolyglucoside surfactants; and 5% to 25% w/w of oil. The composition is prepared with a formulation to produce a fungicide product which is effective in controlling the target microbial agent, easy to handle and apply, have longer shelf life, free from undesirable side effects and environmental friendly.